What does Atlantic Forest soundscapes can tell us about landscape? - Marina D.A. Scarpelli (Elsevier, 2021)
The ecoacoustics approach for environmental recordings analysis is used to understand and identify big ecological patterns related to different sound sources, like animals, humans and the environment itself. Sounds can vary according to several features that can be on its surroundings or far away, therefore they are very much reliant on scale. Because humans are changing the environment so much and we cannot account for all those changes in the same speed as they happen, we need fast evaluation tools, such as remote sensing and acoustic monitoring (considered the equivalent of spatial remote sensing for sounds). Considering that the scale of effect was never measured for soundscapes before, we aimed to see in what scale different acoustic indices were responsive. Also, we tested how acoustic indices are influenced by natural vegetation cover. We recorded environmental sounds in Atlantic Forest fragments during three months on the rainy season. Then we calculated different acoustic indices and the percentage of natural vegetation cover in different scales. Our results corroborated our initial hypotheses: different indices respond to different scales and their medians varied according to the amount of vegetation cover on the surroundings. More studies are needed with less fragmented areas, to test indices behaviour in a continuum, but we consider this work an important starting point to understand acoustic indices behaviour in tropical areas, especially in such degraded and threatened area as Atlantic Forest.